(untitled) (Journal of Pharmaceutical Negative Results, 2022)
For navigation applications, a dual band fractal shaped microstrip patch antenna is developed and simulated. By employing fractal shape,dual-band features are produced. The proposed antenna operates at L5 (1.176GHz) and S(2.492GHz) bands. With the aid of the HFSS EMtool, the proposed antenna is simulated. Low-cost FR4 epoxy serves as the substrate material for the suggested antenna. The circularly polarised, fractal-shaped micro-strip patch antenna is fed using a coaxial cable. Various other properties like return loss, VSWR, axial ratio, gain and radiation patterns are obtained and discussed.